Improving the measurement of intrinsic foot muscle morphology and composition from high-field (7T) magnetic resonance imaging. (July 2022) - Franettovich Smith, Melinda M.; Mendis, M. Dilani; Weber, Kenneth A.; Elliott, James M.; Ho, Ray; Wilkes, Margot J.; Collins, Natalie J.
Abstract: Magnetic resonance imaging (MRI) can be used to quantify intrinsic foot muscle morphology and composition. Due to the high spatial resolution required to adequately capture the architecturally complex anatomy, manual segmentation is time consuming and not clinically feasible. The aim of this study was to evaluate if a reduced number of MRI slices can be used to accurately estimate intrinsic foot muscle volume and composition. A three-dimensional 2-point Dixon sequence of the whole foot was acquired at 7-Tesla for thirteen asymptomatic individuals and twenty individuals with plantar heel pain. Slice intervals of 2, 3, 5, 10, 15 and 30 were used to calculate alternative muscle volume and composition, and were compared to reference values calculated from every available slice. Agreement between methods was assessed by calculating mean differences and 95% limits of agreement, and inspection of Bland –Altman plots. In both groups, slice intervals of 2, 3 and 5 provided excellent precision for all muscles (measurement error < 1%). Larger slice intervals of 10, 15 and 30 provided excellent precision for some muscles, but for other muscles (e.g. small forefoot muscles), error was up to 7.3%. Bland–Altman plots showed no systematic measurement bias. This study provides a quantitative basis for selecting a reduced number of slices to measure intrinsic foot muscle volume and composition from MRI. A slice interval of 10 may provide a balance between efficiency (36 mins vs. 6 h) and accuracy (error < 2.4%) across all intrinsic foot muscles in asymptomatic individuals and those with plantar heel pain.